Stabilization of serum alkaline phosphatase in hemodialysis patients by implementation of local chronic kidney disease-mineral bone disorder management strategy: A quality improvement study - Kyubok Jin; Tae Hyun Ban; Ji Yong Jung; Ae Jin Kim; Yaerim Kim; So-Young Lee; Dong Ho Yang; Bum Soon Choi; Kook-Hwan Oh; Jieun Kim; Young Joo Kwon; Jong Wook Choi; et al. (The Korean Society of Nephrology, 2018)
Background : The aim of this study is to narrow the gap between global guidelines and local practices, we recently established domestic recommendations by adapting the international guidelines for management of chronic kidney disease-mineral bone disorder (CKD-MBD) in patients on maintenance hemodialysis (MHD). This study was undertaken to determine whether application of this guideline adaptation was associated with improved serum mineral profiles in patients with CKD-MBD. Methods : A total of 355 patients on MHD were enrolled from seven dialysis units. After adhering to our strategy for one year, serum phosphorus, calcium, intact parathyroid hormone (iPTH), and alkaline phosphatase (AP) levels were compared with the baseline. The endpoint was improvement in the proportion of patients with serum mineral levels at target recommendations. Results : The median serum phosphorus level and proportion of patients with serum phosphorus within the target range were not changed. Although the median serum calcium level was significantly increased, the proportion of patients with serum calcium within the target range was not significantly affected. The proportion of patients with serum iPTH at the target level was not altered, although the median serum iPTH was significantly decreased. However, both median serum AP and the proportion of patients with serum AP at the target level (70.4% vs. 89.6%, P ＜ 0.001) were improved. Conclusion : In our patients with MHD, serum mineral profiles were altered and the serum AP level stabilized after implementing our recommendations. Long-term follow-up evaluations are necessary to determine whether uremic bone disease and cardiovascular calcifications are affected by these recommendations.